(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article briefly examines the practical activities of the Jadid movement. National development, realized in our life today, draws strength from the high spirituality, traditions and customs of our people, formed over centuries, and the immortal heritage of our great ancestors. The article also discusses how the ideas of the Jadidists, as part of this heritage, serve as an important source in the development of our national spirituality.